Effect of customer involvement on co-creation of services: A moderated mediation model. (November 2021) - Cheung, Millissa F.Y.; To, W.M.
Abstract: The study explored the influence of customer involvement on co-creation directly and indirectly through three customer engagement dimensions, namely identification, interaction, and absorption from lens of customer-dominant logic and stimulus-organism-response framework. Data were collected from 211 Chinese service customers in Hong Kong. Results of IBM SPSS PROCESS models showed that customer involvement influenced co-creation directly and indirectly through absorption and interaction, but not identification. Customer involvement was found to exert a greater impact on co-creation of services for those with a high rather than low relation orientation. Thus, service providers should utilize mass media effectively to arouse customers' feelings of relevance and important of services to them. They should also interact with customers continuously through social media that can be enhanced by various kinds of immersion technology. Highlights: Customer involvement influenced service co-creation through customer engagement. Absorption and interaction mediated the involvement-service co-creation link. Identification failed to mediate the involvement-service co-creation link. Relation orientation moderated the effect of involvement on co-creation.